The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1993
DOI: 10.1103/physrevlett.71.1047
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen adsorption on Co(101¯0): Different reconstruction behavior of hcp (101¯0) and fcc(110)

Abstract: Co(lOTO) with close-packed rows separated by the oaxis distance is a hep analog to fee (110). In contrast to the (2x1) missing-row (MR) structures formed upon oxygen adsorption on several fee (110) surfaces, a novel type of MR reconstruction is revealed by scanning tunnel microscopy and low energy electron diffraction on Co(lOTO): The low coverage (2x1) O phase constitutes a double-layer MR structure with (2*1) MR configurations in the two topmost Co layers; it develops locally by moving every other atom of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 22 publications
(29 reference statements)
0
19
0
1
Order By: Relevance
“…In an earlier LEED study, Schwarz et al [184] found that the Co(101 -0)-(2Â1)p2mg-2O phase is developed from the p(2Â1)-O or the c(2Â4)-4O phase by increasing the oxygen coverage at higher temperature. Based on the STM observations, Koch et al [42,43] proposed several models for the reconstructed O-Co(101 -0)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier LEED study, Schwarz et al [184] found that the Co(101 -0)-(2Â1)p2mg-2O phase is developed from the p(2Â1)-O or the c(2Â4)-4O phase by increasing the oxygen coverage at higher temperature. Based on the STM observations, Koch et al [42,43] proposed several models for the reconstructed O-Co(101 -0)…”
Section: Discussionmentioning
confidence: 99%
“…For instance, O-Cu pairing chains form on the Cu(001)-( ffiffi ffi 2 p  2 ffiffi ffi 2 p )R45 -2O surface and the 'dumb-bell' protrusions are as high as 0.45 Å [36]. In contrast, zigzagged O-O chains form between two Co rows along the close-packed direction on the Co(101 -0)-c(4Â2)-4O surface [42]. The 'honeycomb' protrusions on the O-Co(101 -0) surface are up to 1.0 Å [43].…”
Section: Alternation Of Atomic Valenciesmentioning
confidence: 99%
“…For example, the hcp trough-and-row surface Co(101 0) forms O-Co pairing chains in the c(4ϫ2) O-Co(101 0) surface reconstruction, which are oriented along the close-packed directions and consist of protrusions of up to 1 Å height. 20 The resulting reconstructed phases after exposing the fcc trough and row ͑Ag,Ni,Cu͒ ͑110͒ surfaces to oxygen possess a high degree of similarity in the sense that they are all stabilized by single O-M-O strings. However, the O-M chains are running in these cases perpendicular to the close-packed directions in a so-called missing-row-added-row structure.…”
Section: Oxygen-induced Surface Reconstruction On the Mo(112) Surfacementioning
confidence: 99%
“…In contrast to the (2 9 1) MR reconstruction patterns on the O-(Cu, Ni, Ag, Pt)(110) surfaces, three intriguing superstructures show in sequence on the O-Co(1010) surface [109][110][111][112][113] and two on the O-Ru(1010) surface [114][115][116]. From the standpoint of microscopy and crystallography, O-(Co, Ru)(1010) multiphase ordering has been well identified.…”
Section: Stm Morphology and Crystallographymentioning
confidence: 99%
“…In an earlier LEED study, Schwarz et al [112] found that the Co(1010)-(2 9 1)p2mg-2O phase is developed from the p(2 9 1)-O or the c(2 9 4)-4O phase by increasing the oxygen coverage at higher temperatures. Based on STM observations, Koch et al [109,110] proposed models for the reconstructed O-Co(1010) phases. LEED calculations [113] suggested that in the final (2 9 1)p2mg-2O phase, oxygen occupies the threefold-coordinated fcc(111) facet site and bonds to two Co or Ru atoms in the first atomic layer and one Co or Ru atom in the second, this being the same as that occurring on the O-(Rh, Pd)(110) surface.…”
Section: Stm Morphology and Crystallographymentioning
confidence: 99%